Using LMS Schoology to Improve Learning Outcome of English Teacher Training Participants - yanto, Wida (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
Abstract This research was based on the teaching and learning process now in the education and training field which most of it still tends to be done conventionally. Learning through E-learning can overcome the constraints of space and time. Widyaiswara (Instructor) and training participants can make the learning process both synchronous (direct), and asynchronous (indirectly) through the virtual world. This study is intended to describe the influence of LMS Schoology in improving the learning outcomes of English Training participants in Religious Education and Training Center (BDK) Surabaya. Formulation of the problem “Is there a significant and positive influence on the use of LMS Schoology on Improving Learning Outcomes of English Teacher Training Participants?” The research method used is pre-experimental one group pretest-postets with regression analysis. Regression analysis is used to find out how much influence the independent variable has on the increase in the dependent variable. The results showed that after teaching and learning process was carried out with the LMS Schoology application media there is a significant and positive influence on the use of LMS Schoology to increase the learning outcomes of English Teacher Training participants and the amount of the influence of the LMS Schoology usage variable on the increase participant learning outcomes is 77.4%. That is, the effect of LMS Schoology on the learning outcomes of training participants is 77.4%. Keywords: E-learning, LMS Schoology, learning outcomes